Intelligent mechanical manufacturing technology based on intelligent manufacturing technology - Zheng Kang (MATEC Web of Conferences, 2023)
With the development of intelligent manufacturing technology, the application of intelligent machinery manufacturing technology has been widely promoted. Intelligent machinery manufacturing technology is a technology that integrates advanced manufacturing technology and intelligent control technology. It can realize the intelligent control of the entire manufacturing process, improve the manufacturing efficiency and product quality, and reduce the manufacturing cost. Based on intelligent manufacturing technology, intelligent machinery manufacturing technology has been developed rapidly and has been widely applied in various fields such as automotive, aviation and so on. It can achieve the goals of automation, intelligence, high efficiency, and personalization, and promote the development of various industries towards intelligent manufacturing. However, there are still challenges in the development and application of intelligent machinery manufacturing technology, such as the high cost of equipment, the difficulty in controlling the manufacturing process, and the lack of skilled workers. Future research should focus on solving these challenges and promoting the further development and application of intelligent machinery manufacturing technology.